Faktor yang Mempengaruhi Tingkat Partisipasi Ibu Dalam Posyandu Balita Dusun I Desa Jatikesuma, Kecamatan Namorambe - Khairi Rizki Hidayani; Nahda Aurallia; Putri Amanda Rizki; Adinda Afifah; Raisah Adilla; Adinda Tri Oktaviani (Universitas Batanghari Jambi, 2023)
Posyandu is a form of effort to improve health based on community resources or UKBM. Implemented and carried out in empowered communities as facilities that can facilitate the community in achieving a healthy and prosperous life through health services for mothers, babies and toddlers. The purpose of this study was to determine the level of mother's participation in toddler posyandu activities and what are the factors that influence it. This research was conducted qualitatively using primary data and secondary data. This research was conducted in Jatikesuma Village, Namorambe. With a total population of infants and toddlers in Jatikesuma Village as many as 546. The number of samples in August were 49 children from 125 children registered at Posyandu Dusun I. Samples were taken and would become respondents in this study conducted by cross sectional and interview methods. The results showed that the variable gender was in the female category with a total percentage of 63%, the variable age of the baby with a range of 0-2 years with a total percentage of 80%, the variable of baby's weight with a range of 1-10 kg with a total percentage of 55%.